2022
DOI: 10.3390/cancers14071784
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer and Sleep Disorders: A Systematic Review

Abstract: Prostate cancer (PCa) treatment involves multiple strategies depending on the disease’s stage. Androgen deprivation therapy (ADT) remains the gold standard for advanced and metastatic stages. Sleep quality has been suggested as being additionally influenced also by local radiotherapy, prostatectomy and androgen-receptor (AR)-targeted agents. We performed a systematic review exploring the landscape of studies published between 1 January 1990 and 31 July 2021, investigating sleep disturbances in PCa patients rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Another citing article in this cluster was written by Sparasci et al [ 64 ]. They reviewed sleep disturbances and prostate cancer, paying particular attention to prostate cancer treatments and any potential sleep-related effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another citing article in this cluster was written by Sparasci et al [ 64 ]. They reviewed sleep disturbances and prostate cancer, paying particular attention to prostate cancer treatments and any potential sleep-related effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hot flashes can be associated with sleep disturbance and may lead to a deterioration in quality of life. 85 Moreover they may decrease compliance to ADT and are a major contributor to its discontinuation. 24 …”
Section: Hot Flashesmentioning
confidence: 99%
“…It is estimated that 25% to 40% of prostate cancer patients experience insomnia, and ADT, radiation therapy, and prostatectomy are all believed to play a role. 107 , 108 There is certainly a lack of trials examining sleep disorders in prostate cancer patients, and thus, a dearth of prospective data on the topic. From reviewing the limited retrospective literature, as Sparasci et al most recently completed, 14 of 16 trials demonstrated development of sleep disorders or changes in sleep quality in this patient population.…”
Section: Androgen-deprivation Therapy and Insomniamentioning
confidence: 99%
“…From reviewing the limited retrospective literature, as Sparasci et al most recently completed, 14 of 16 trials demonstrated development of sleep disorders or changes in sleep quality in this patient population. 107 Hot flashes and nocturia are prominent factors that play a role in contributing to insomnia in men with prostate cancer undergoing treatment. Patients on ADT report greater hot flash incidence and more severe and clinically significant sleep disturbances when measured on the Insomnia Severity Index.…”
Section: Androgen-deprivation Therapy and Insomniamentioning
confidence: 99%